Professionalism - Cribb, Alan; Gewirtz, Sharon 1964- (Cambridge, United Kingdom Polity Press, 2015)
"Professionalism is a complex and highly disputed idea of crucial importance in a range of fields, not least health and social care. It can inspire people by reminding them of workplace ideals and the value of occupational expertise. But it can also feel threatening and de-motivating; for example, if it is used to demand ever more from people working in very challenging circumstances. The language of professionalism can evoke a special relationship of trust between service users and practitioners. But it can also suggest a social distance between two classes of people; high status professionals and their lower status 'non-professional' clients.This book is an original and accessible guide to these ambiguities and complexities. Cribb and Gewirtz clarify the nature of professionalism and explain and defend its importance, providing an understanding of, and an analytical engagement with, both idealistic and critical perspectives. In addition, the authors assess the implications of contemporary policy trends for professional work, showing how they may be radically altering our understanding of the 'good' professional.This inviting and reflective study draws upon examples and case studies and weaves in a range of relevant theoretical concepts and perspectives. Written in a style that encourages and supports further reflection on this complex topic, Professionalism/ is the only book of its kind for practitioners, researchers and students in health and social care"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Health Occupations